Clinical and Immunological Beneficial Effects of Phyto V7 Consumption by HIV-1 Seropositive Individuals - J. R Wernik; G. Borkow; W. F. Goldman; A. C. Elias (Journal of Clinical Research In HIV AIDS And Prevention, 2015)
Phytochemicals (PHT) are a large group of biologically active plant chemicals that may have positive effects on human health such as immune system stimulation, down regulation of inflammatory responses, radical scavenging activities, cell repair function, and antibacterial and antiviral activity. In this proof of principle 6 months study, the effects of supplementing a PHT mix, Phyto V7, to HIV-1 seropositive individuals and AIDS patients were examined. Individuals with CD4+ T-cells below 350 counts/mm3were assigned to one of the following treatments: CG1 - no treatment, CG2 - only highly active antiretroviral treatment (HAART), TG1 - only Phyto V7, and TG2- both Phyto V7 and HAART. After 3 months of treatment there were approximately (-)1%, 1%, 2% and 4% increase in the mean weight of the CG1, CG2, TG1 and TG2 groups, respectively. The tendency for the body mass index (BMI) was similar. The CD4+ counts increased by 13%, 39%, 53% and 35%, respectively. Similar trends were noted after 6 months with 2%, 79%, 53% and 69% increases in the CD4+ counts, respectively. There was a significant reduction in viremia only in groups receiving HAART. Overall better results were obtained in the group of patients receiving both HAART and Phyto V7, in which the mean weight increased by 5.7% and the CD4+ T-cell counts increased by 69% after 6 months. This study indicates that providing Phyto V7 to HIV-1 seropositive individuals and AIDS patients, receiving or not receiving HAART, improves their physical wellbeing and CD4+ counts, enabling them to cope better with the viral infection.
Keywords: Phytochemicals